ANALISIS KIMIA DUA PULUH TUJUH JENIS KAYU JAWA BARAT - Kayano Purba; Endang Sumarna (Pusat Penelitian dan Pengembangan Hasil Hutan, 1987)
Chemical analyses of wood species from different islands of Indonesia has been started by several workers. Most of the species studied were obtained from East Kalimantan, South Kalimantan, Central Kalimantan, East Java and South Sumatera. The analyses comprised the determination of cellulose, lignin, pentosan, ash, extractives and the solubility in one percent of sodium hydroxide. These analyses were conducted to determine their basic characteristics and ultimate uses of the wood. In this report the result of chemical analyses of 27 wood species from West Java are presented as supplementing reference to the previous ones.The analyses reveal that the cellulose content ranges from 40.99-55.54 percent, pentosan from 12.49-19.54 percent and lignin from 17.20-28.86percent.The ash and silica content vary considerably from 0.19-1.43 percent and from 0.05-0.79 percent, respectively.The solubility in cold water varies from 0.11-7.20 percent, in hot water from 2.18-10.44 percent, in alcohol benzene (1 : 2) from 0.54-8.70 percent, and in one percent sodium hydroxide solution from 11.01-37.94 percent.